2021
DOI: 10.3389/fmicb.2021.663744
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of a High-Yield Ethyl Caproate-Producing Yeast From Daqu and Optimization of Its Fermentation

Abstract: Baijiu is an important fermented product in China. A yeast named YX3307 that is capable of producing a large amount of ethyl caproate (EC) was isolated from Daqu, a crude fermentation starter for Baijiu. This yeast was identified as Clavispora lusitaniae on the basis of its morphological properties, physiological and biochemical characteristics, and 26S rDNA sequence. Single-factor experiments were conducted to obtain the optimum fermentation conditions for EC production by YX3307. The highest EC yield (62.0 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 62 publications
(69 reference statements)
3
39
0
Order By: Relevance
“…Bacillus spp., Alcaligenes spp., and Pseudomonos spp., of bacteria and Penicillium spp., Fusarium spp., Aspergillus spp., of fungi are screened as candidates for large scale of the production of lipases mentioned above [ 77 ]. However, the selection and modification of high-yield ethyl caproate strains mainly focus on Saccharomyces cerevisiae [ 78 80 ]and Monascus purpureus [ 81 83 ]. In our study, we established the closer relationship between 21 novel genus of bacterium (such as Aeriscardovia , Atopobium and Paracocccus ) and the formation of ethyl hexanoate after P value adjust ( Fig 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…Bacillus spp., Alcaligenes spp., and Pseudomonos spp., of bacteria and Penicillium spp., Fusarium spp., Aspergillus spp., of fungi are screened as candidates for large scale of the production of lipases mentioned above [ 77 ]. However, the selection and modification of high-yield ethyl caproate strains mainly focus on Saccharomyces cerevisiae [ 78 80 ]and Monascus purpureus [ 81 83 ]. In our study, we established the closer relationship between 21 novel genus of bacterium (such as Aeriscardovia , Atopobium and Paracocccus ) and the formation of ethyl hexanoate after P value adjust ( Fig 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…This was the first identification of an A. niger species for efficient fatty acid ethyl ester synthesis in an aqueous-phase system. So far, only a few studies reported the ester synthesis of fungal species from baijiu in the aqueous phase system, such as M. purpureus and C. lusitaniae (Fan et al, 2021;Xu et al, 2021b). It was not a frequently identified property of the microorganisms from baijiu.…”
Section: Methodsmentioning
confidence: 99%
“…Although microorganisms are recognized to play an important role in fatty acid ethyl ester synthesis during baijiu fermentation, studies about the related microorganisms are still scarce. Taking strong-flavor baijiu as an example, many microorganisms are involved in the fermentation process, while only Burkholderia pyrrocinia , Clavispora lusitaniae , Lichtheimia ramosa , and Monascus purpureus were reported with the ability to synthesize fatty acid ethyl esters ( Chung et al, 2017 ; Fan et al, 2020 , 2021 ; Xu et al, 2021b ). In addition, although some of these microorganisms promoted ester synthesis in practical application, bottleneck problems existed such as unstable ester concentrations among batches and unclear technical conditions for the actual application of these species ( Xu et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the raw materials are quite different, wine is usually fermented through microorganisms using the sugars in raw materials, such as glucose, fructose in fruit, and lactose in milk. Although the sugars in the grain exist in the form of macromolecule polysaccharides (e.g., starch), during the brewing process of grain wine, polysaccharides are primarily converted into small molecule sugars by enzymatic hydrolysis, and then converted into ethanol by yeast [ 2 ].…”
Section: Introductionmentioning
confidence: 99%